Upon the Altar of Work : Child Labor and the Rise of a New American Sectionalism - Wood, Betsy (Book collections on Project MUSE., 2020)
"Rooted in the crisis over slavery, disagreements about child labor broke down along sectional lines between the North and South. For decades after emancipation, the child labor issue shaped how Northerners and Southerners defined fundamental concepts of American life such as work, freedom, the market, and the state. Betsy Wood examines the evolution of ideas about child labor and the on-the-ground politics of the issue against the backdrop of broad developments related to slavery and emancipation, industrial capitalism, moral and social reform, and American politics and religion. Wood explains how the decades-long battle over child labor created enduring political and ideological divisions within capitalist society that divided the gatekeepers of modernity from the cultural warriors who opposed them. Tracing the ideological origins and the politics of the child labor battle over the course of eighty years, this book tells the story of how child labor debates bequeathed an enduring legacy of sectionalist conflict to modern American capitalist society"--